The role of M3 receptors in regulation of electrical activity deteriorates in the rat heart during ageing - Svetlana V. Tapilina; Alexandra D. Ivanova; Tatiana S. Filatova; Pavel A. Galenko-Yaroshevsky; Denis V. Abramochkin (Current Research in Physiology, 2022)
Ageing is a complex process which affects all systems of the organism and therefore changes the environment where the heart is working. In this study we demonstrate the ageing-related changes in the mechanisms of parasympathetic regulation of mammalian heart. Electrophysiological effects produced by selective activation of M3-cholinoreceptors were compared in isolated cardiac preparations from young adult (4 months), adult (1 year) and ageing (2 years) rats using sharp glass microelectrode technique. M3-receptors were activated with muscarinic agonist pilocarpine (10-5M) in the presence of selective M2 antagonist AQ-RA741 (10-7M). In atrial and ventricular myocardium from young rats M3 stimulation induced shortening of action potentials(APs), while no significant effect was observed in both elder groups. The main mechanism of M3-induced AP shortening is inhibition of L-type Ca2+ current, estimated using whole-cell patch-clamp. It was negligible in atrial myocytes from ageing animals in comparison with young rats. The loss of sensitivity to stimulation of M3-receptors is due to decrease in M3 gene expression, shown by RT-PCR both in atrial and ventricular samples from ageing rats. Thus, in ageing rat heart M3-receptors are down-regulated and not involved in regulation of electrical activity.